1994
DOI: 10.1073/pnas.91.25.11816
|View full text |Cite
|
Sign up to set email alerts
|

Observation of binding and polymerization of Fur repressor onto operator-containing DNA with electron and atomic force microscopes.

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 31 publications
4
26
2
Order By: Relevance
“…The physiological relevance of oligomeric Fur binding at high protein concentrations is not certain. Whereas the dimeric Fur can oligomerize both in the presence and absence of DNA3839, Streptomyces dimeric Zur in our study did not form oligomers in the absence of DNA. In the case of X. campestris Zur7, the binding site upstream of the putative efflux gene showed a different sequence motif distant from the Zur-box consensus found in zinc-uptake genes.…”
Section: Discussioncontrasting
confidence: 64%
“…The physiological relevance of oligomeric Fur binding at high protein concentrations is not certain. Whereas the dimeric Fur can oligomerize both in the presence and absence of DNA3839, Streptomyces dimeric Zur in our study did not form oligomers in the absence of DNA. In the case of X. campestris Zur7, the binding site upstream of the putative efflux gene showed a different sequence motif distant from the Zur-box consensus found in zinc-uptake genes.…”
Section: Discussioncontrasting
confidence: 64%
“…It has been reported that Fur may have more than one binding site at a given promoter, and these often constitute a primary high‐affinity site and a secondary proximal lower affinity site (de Lorenzo et al ., 1987; Brickman et al ., 1990; Tardat and Touati, 1993; Ochsner et al ., 1995; Chai et al ., 1998). Footprinting analyses have also shown that, at higher concentrations of protein, the protected regions can extend from the specific binding sites over the DNA (Frechon and Le Cam, 1994;Escolar et al ., 2000), and visualization of these complexes demonstrated that the protein polymerizes on its binding site through Fur–Fur interactions wrapping helically around the DNA (Frechon and Le Cam, 1994; Le Cam et al ., 1994). In addition, it has been shown that, in E. coli , Fur binding does not bend DNA, both through visualization of rigid Fur–DNA complexes (Le Cam et al ., 1994) and by circular permutation experiments (de Lorenzo et al ., 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Footprinting analyses have also shown that, at higher concentrations of protein, the protected regions can extend from the specific binding sites over the DNA (Frechon and Le Cam, 1994;Escolar et al ., 2000), and visualization of these complexes demonstrated that the protein polymerizes on its binding site through Fur–Fur interactions wrapping helically around the DNA (Frechon and Le Cam, 1994; Le Cam et al ., 1994). In addition, it has been shown that, in E. coli , Fur binding does not bend DNA, both through visualization of rigid Fur–DNA complexes (Le Cam et al ., 1994) and by circular permutation experiments (de Lorenzo et al ., 1988). In view of these reports, the pattern of DNase I protection and hypersensitivity observed on the pfr promoter DNA of H. pylori suggests a different mechanism of binding.…”
Section: Discussionmentioning
confidence: 99%
“…Fur is able to fine-tune the transcription of the mrkHI operon in response to the presence of iron (10). It is known that the ␣-CTD of RNAP interacts with UP elements in the minor groove of DNA (44,49) whereas Fur binds to the major DNA groove of the Fur box (50). It is therefore possible that the regulatory region of the mrkHI operon is able to accommodate both the ␣-CTD of RNAP and Fur.…”
Section: Figmentioning
confidence: 99%